Drawing a clear mechanistic picture for the aggregation-induced emission process. (25th April 2019) - Zhang, Haoke; Liu, Junkai; Du, Lili; Ma, Chao; Leung, Nelson L. C.; Niu, Yingli; Qin, Anjun; Sun, Jingzhi; Peng, Qian; Sung, Herman H. Y.; Williams, Ian D.; Kwok, Ryan T. K.; et al.
Abstract : Excited-state "double-bond" torsion plays an important role in the nonluminescent behaviour of a stilbene-based twisted isomer. Abstract : Fluorescence is a widely used method to monitor many biological and abiological processes as well as being famous for its use in display devices. Currently, its wavelength can be accurately tuned in organic fluorophores by regulating their conjugation length. However, emission efficiency is still an experiential parameter. In this work, we investigate the photophysical properties of two stilbene-based isomerides. The different positions of one methyl group make di- o -methyl substituted 2, 4, 6-TMe-DPE more twisted than mono- o -methyl substituted 2, 4, 5-TMe-DPE. Experimental results show that the twisted structure is nonluminescent in solution and exhibits a typical aggregation-induced emission effect. However, the other planar isomer shows strong emission both in solution and in aggregate states. Steady-state and time-resolved spectroscopy, and quantum mechanical calculation suggest that nonradiative decay is predominant in 2, 4, 6-TMe-DPE and that excited-state double-bond torsion contributes a lot to the nonradiative decay channel. This work draws a clear photophysical picture for the aggregation-induced emission process and enables the luminescent behavior to become predictable and controllable.